Development of a pressure control algorithm without a pressure sensor for a four-wheel drive unit. (May 2018) - Lee, Kangneoung; Ha, Hyunjong; Ahn, Sunghyun; Hong, Sungwha; Kang, Heon; Heo, Seungjoon; Kim, Hyunsoo
This article proposes a pressure control algorithm without a pressure sensor for a four-wheel-drive unit. To develop the control algorithm, dynamic models of the four-wheel-drive unit were obtained, including the motor, pump, and clutch. For feedback control, a first-order adaptive transfer function of the modified motor speed was proposed to fulfill the transient response characteristics, and the motor input voltage generated the demanded pressure at steady state in the feedforward control. The coefficientα of the adaptive transfer function was obtained with weight factorsW 1 andW 2 considering the pressure difference and temperature. The performance of the proposed pressure control algorithm without a pressure sensor was evaluated by experiments at various operating temperatures. It was found that the actual pressure closely followed the demanded pressure with an acceptable error at steady state and within an acceptable rising time in a transient state.